The woodshed mystery eaudiobook - Warner, Gertrude Chandler (The Boxcar Children, 2012)
The Alden children are staying at the New England farmhouse where their grandfather grew up. There are many stories and legends about the old farm, and there's a woodshed near the house that holds a surprising secret... a secret that dates all the way back to the Revolutionary War!